School wellbeing siswa fullday school dan siswa regular school - Nuril Istiqomah; Agustin Rahmawati (University of Merdeka Malang, 2020)
Full-day school program is often associated with many problems in children, including perhaps physical and psychological fatigue, or a reduced intensity of interaction between siblings, which in fact will result in not achieving the comfort of school. This research has a purpose to find out whether there are differences in school wellbeing among students who attend full-day school and regular school.. The subjects in this study were 127 students of SMPN 2 Gempol who took full-day and regular education. The sampling technique was proportional stratified random sampling. The school wellbeing scale was used to collect data. The results of data analysis using the independent t-test obtained t hit 2,304 with a significance of 0.023. The mean of full-day school students 127 and regular school students 133. The results of data analysis show that there are differences in school wellbeing between full-day school students and regular school students, where regular school students have better school wellbeing compared to full-day school students, meaning that the hypothesis is accepted.